IMPROVING DIDACTICAL SUPPORT FOR LOGICAL THINKING CLASSES (Scientific journal of the Fergana State University, 2024)
This article expresses opinions on the need to improve didactic support for classes in preschool educational organizations and teaching logical thinking.